IMPLEMENTATION OF JJ ROUSSEAU'S EDUCATIONAL THEORY AT THE CENTRAL INSTITUTE FOR AL-QURÁN SCIENCE EDUCATION, NURUL JADID ISLAMIC BOARDING SCHOOL - Khoiroh, Ummul; Hidayat, M.Noer Fadli; Holifah, Holifah; Rahmatillah, Alda Novita (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research analyzes the integration of Jean-Jacques Rousseau's educational theory into the Islamic education system at the Nurul Jadid Islamic Boarding School, Probolinggo. Rousseau's theory, which emphasizes freedom, natural development, and respect for individual uniqueness, is considered relevant in strengthening the learning of the Koran and the formation of Islamic character. With a qualitative approach, this research explores the application of active learning, direct experience, and the development of students' potential in the context of Islamic values. The implementation of this theory will provide a more expansive space for intellectual exploration and increase in-depth understanding of Islamic teachings. The research results show that Rousseau's approach can support a relevant natural-based curriculum and strengthen the formation of Islamic character. Challenges arise in aligning modern educational concepts with traditional methods of Islamic education, but collaborative efforts are believed to be able to overcome these obstacles. The integration of Rousseau's theory creates a holistic foundation for Islamic education, enabling the Nurul Jadid Islamic Boarding School to become an educational model that is adaptive to current developments.